Socio-economic Determinants of Age at First Marriage of Rural Women: A Statistical Analysis (International Journal of Engineering and Computer Science, 2017)
In this study it was our aim to investigate the socio-economic determinants of age at first marriage of the rural women of Kushtia district, Bangladesh. A sound methodology was adapted to gather information regarding age at first marriage and variables related to other socio-demographics. Cox proportional hazard regression analysis was applied to the data set containing 444 observations from different village of the district. The mean age at first marriage of the study women was found to be 15.8 years, which is very close that of national level. Findings revealed that woman‟s educational attainment and pre-marital work status significantly delayed the timing of marriage. Parents‟ economic status and respondents‟ birth order had the most significant effect on marital timing. The multivariate statistical analyses also identified several variables as important determinants of marriage timing for the study women childhood place of residence, father‟s literacy, father‟s survival status and mother‟s age at first marriage. The findings of the study may provide a clue to the rising age at first marriage of the disadvantaged rural women.